Analysis of the Effect of Brand Equity Dimensions on Honda Vario Purchase Decisions Among FEB ULB Students - Novita Lasri KS; Elida Florentina Sinaga Simanjorang; Yudi Prayoga (PT Mattawang Mediatama Solution, 2022)
This research applies quantitative descriptive nature, which aims to determine the effect of brand awareness, brand associations, perceived quality and loyalty on purchasing decisions. The population in this study were students who used Honda Vario among FEB ULB as many as 1143 people. Then, the sample in this study was 92 students and used the Slovin formula. The data analysis used is descriptive quantitative, multiple linear analysis, hypothesis test and classical assumption test. And the results of the multiple linear equation research show that Y= 0.219 + 0.039X 1 + 0.228X 2 + 0.437X 3 + 0.586X 4 + e. The t-test (Partial) shows that brand awareness and brand associations have a positive and not Sig effect, while the perception of quality and brand loyalty has a positive effect and Sig. The f test shows that the research results have a positive influence and Sig on purchasing decisions simultaneously. The R2 test shows that the effect of the independent variable on the dependent variable is 0.634 or 63.4%, and 36.6% is not part of the research variable.